Perancangan Promosi Wisata Pendakian Gunung Merbabu melalui Desa Cuntel - Dawami, Angga Kusuma (Magenta | Official Journal STMK Trisakti, 2019)
Mountaineering travel more year more and more in demand by the public, especially the younger generation. The emergence of climbing themed films, is a bit much affect the interest of people to climb the mountain. Almost the entire mountain can be climbed by hikers, generally increases when the climbing season, including Merbabu. There are five hiking trail that can be an alternative to reach the summit of Mount Merbabu. One of them is the Cuntel village is a village that has a gate official ascent of Mount Merbabu National Park (TNGMb). This paper is a design of a climbing lane exposure in order to increase the potential for tourism in the village Cuntel climbing lane. The result of this design has been used by the manager of the Post Ascent, Ascent village to help promote Cuntel in the tourism sector. ABSTRAK Wisata pendakian gunung semakin tahun semakin banyak diminati oleh masyarakat, terutama generasi muda. Munculnya film-film bertema pendakian, juga sedikit banyak mempengaruhi minat orang untuk mendaki gunung. Hampir seluruh gunung-gunung yang bisa didaki oleh pendaki, umumnya meningkat saat musim pendakian, termasuk juga Merbabu. Terdapat lima jalur pendakian yang dapat menjadi alternatif untuk mencapai puncak Gunung Merbabu. Salah satunya adalah Desa Cuntel yang merupakan salah satu desa yang memiliki gerbang pendakian resmi dari Taman Nasional Gunung Merbabu (TNGMb). Tulisan ini merupakan paparan perancangan jalur pendakian guna meningkatkan potensi wisata di jalur pendakian Desa Cuntel. Hasil perancangan ini telah digunakan oleh pengelola Pos Pendakian, untuk membantu mempromosikan Pendakian Desa Cuntel dalam sektor pariwisatanya.